Penerapan Media Video Tutorial untuk Meningkatkan Hasil Belajar IPA Peserta Didik Kelas IX SMP Islam Al-Azhar24 Makassar (Studi pada Materi Pokok Teknologi Ramah Lingkungan) - Bietnaryen Virgonius Banga; Salma Samputri; Sitti Rahma Yunus (Universitas Negeri Makassar, 2024)
This study research to determine: (1) the level of students' science learning outcomes before implementing video tutorials in learning, (2) the level of students' science learning outcomes after implementing vi deo tutorials in learning, (3) increasing students' science learning outcomes after implementing videos tutorials in learning, (4) whether or not there is a significant increase in students' science learning outcomes after implementing video tutorials in learning. This research is a pre-experiment research with a One Group Pretest-Posttest Design. The population of this study was all students in class IX of Al-Azhar Islamic Middle School, totaling 44 students. The sample for this research was selected using a purposive sampling technique with criteria in accordance with the researcher's objectives with the sample or class requirements selected being more conducive to research with a total of 22 students. The instrument in this research is a multiple choice test question. Data analysis techniques are descriptive and inferential. The results of this research can be concluded: the results of the descriptive analysis (1) the level of students' science learning outcomes before implementing video tutorials in learning is very low with an average value of 39.24, (2) the level of students' science learning outcomes after implementing video tutorials in learning is moderate with an average value of 71.36, (3) the increase in students' science learning outcomes after implementing video tutorials is moderate with an average N-Gain value of 0.53. The results of the inferential analysis show that (4) there is a significant increase in students' science learning outcomes after implementing video tutorials in learning.